Strategi Pengembangan Profesionalisme Guru di Era Digital: Tantangan dan Peluang - Saerang, Hetwi Marselina; Lembong, Jelly Maria; Sumual, Shelty Deity Meity; Tuerah, Roos Marie Stella (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2023)
The goal of the study is to identify methods for fostering teacher professionalism in the digital age, taking-into-account the potential and problems that may arise. A literature review was the research methodology adopted in this study. In this study, papers that are pertinent to the research topic and are required for it were gathered using library research data gathering methodologies. This is accomplished by using Publish or Perish (PoP), which uses the article databases from Google Scholar and Sciendirect for the 2019–2023 period to gather the necessary articles. Three stages make up the research phase used in this study: planning, conducting, and reporting. The article analysis produced 19 journal papers in both English and Indonesian that were pertinent to the research themes. The inference that may be made is that there are both obstacles and opportunities presented by the digital era. To build a plan for enhancing teacher professionalism in the digital age, it is necessary to identify obstacles and make use of numerous opportunities. The current plan involves supervision, KKG, PKG, and MGMP in addition to the implementation of training, workshops, seminars, and certification connected to the production of media, resources, and digital-based subject matter.